2020
DOI: 10.3892/etm.2020.8574
|View full text |Cite
|
Sign up to set email alerts
|

miR‑106b‑5p promotes cell proliferation and cell cycle progression by directly targeting CDKN1A in osteosarcoma

Abstract: MicroRNA (miR)-106b-5p has been reported to act as both an oncogene and tumor suppressor in several tumors. The aim of the present study was to investigate the biological function of miR-106b-5p in osteosarcoma (OS). miR-106b-5p expression was observed to be significantly increased in OS tissues and cell lines. MTT assay and flow cytometry analysis determined that miR-106b-5p inhibitor transfection suppressed OS cell proliferation and induced cell cycle G0/G1 phase arrest. Furthermore, bioinformatics analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Knowledge of the regulation and function of CDKN1A in cancer cells has opened up several areas of investigation and led to novel therapeutic strategies. Some miRNAs have been identified to be associated with CDKN1A expression [ 33–35 ]. The direct binding between miR-520h with CDKN1A was verified by dual-luciferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the regulation and function of CDKN1A in cancer cells has opened up several areas of investigation and led to novel therapeutic strategies. Some miRNAs have been identified to be associated with CDKN1A expression [ 33–35 ]. The direct binding between miR-520h with CDKN1A was verified by dual-luciferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 27 miRNAs were simultaneously identified from the two data sets. MiR-106b-5p, 24 miR-130a-3p, 25 miR-130b-3p, 26 miR-17-5p, 27 miR-19a-3p, 28 miR-19b-3p, 29 miR-301a-3p, 30 miR-4295, 31 and miR-93-5p 32 have been previously shown to be upregulated in OS and play oncogenic roles during cancer progression. In addition, no studies have reported an association of miR-1180-5p, miR-301b-3p, miR-3666, miR-519b-3p, miR-519c-3p, miR-520g-3p, miR-520h, miR-5590-3p, and miR-7114-3p with OS.…”
Section: Linc00839 Acts As a Sponge For Mir-454-3p In Os Cellsmentioning
confidence: 99%
“…BAK localizes to mitochondria, and functions to induce apoptosis. HDAC6 is involved in cell cycle and apoptosis [ 56 ], and CDKN1A and CDK members were critical in cell cycle progression [ 57 , 58 , 59 ]. Therefore, our results suggested that Tucidinostat and DL-sulforaphane suppressed the uLMS proliferation via cell cycle arrest and apoptosis.…”
Section: Resultsmentioning
confidence: 99%